HAK NASABAH PEGADAIAN BILA TERJADI PELELANGAN TERHADAP BARANG JAMINAN - ARDIKA, GEDE TUSAN; TITAWATI, TITIN; LOILEWEN, ALINE FEBRIANY; RAMLI, RAMLI (GANEC SWARA, 2024)
Returns of loan money and capital leases that are not repaid by the specified time limit are carried out through auctions of customer collateral. If by the auction date the pledgor does not carry out his obligations, the collateral will be auctioned by the pledgee. This research aims to find out about the mechanisms and procedures for carrying out auctions for collateral objects. This research is sociological research with a qualitative approach. The data sources used by the author are primary data sources and secondary data sources. The problems that will be discussed in this research are the procedures for carrying out auctions for customer collateral and the obstacles in carrying out auctions. How to protect and overcome obstacles in carrying out auctions for customers' collateral. Auctions of collateral are carried out in 3 stages, namely, auction notification, auction preparation and auction implementation. However, not every auction of collateral can run smoothly, this is due to various obstacles in the implementation of the auction.